HOW EFFECTIVE IS ECLECTIC METHOD TO TEACH ACADEMIC WRITING? - Benny Krisbiantoro; Tri Pujiani (LPPM Universitas Harapan Bangsa, 2020)
The Eclectic Method is a combination of several learning methods to accommodate differences in students’ various characteristics, such as learning styles or preferences, experiences, habits, background, and of course learning abilities. The method employed in this research was a quasi-experimental research with post-test-only non-equivalent control group design. The result of the research findings led to the conclusion that eclectic method was more effective than scientific approach to teach writing for the eighth semester students of the Nursing Study Program, Faculty of Health, Harapan Bangsa University. It was proven that the mean score of the students’ writing in experimental class was 78.19 while the mean score of the students’ writing in control class was 72.14. The t-test result in the research was 2.32 and the t-table is 2.02. It meant that t-test score was higher than the t-table. Based on the research findings, it could be concluded that the use of eclectic method was effective to teach writing for the eighth semester students of the Nursing Department, Faculty of Health, Harapan Bangsa University.